Thermogravimetric analysis of activated carbons, ordered mesoporous carbide-derived carbons, and their deactivation kinetics of catalytic methane decomposition - Shilapuram, Vidyasagar; Ozalp, Nesrin; Oschatz, Martin; Borchardt, Lars; Kaskel, Stefan; Lachance, Robert (Industrial & Engineering Chemistry Research, 2014)
This study presents the deactivation kinetics of methane decomposition for the activated carbons Fluka-05105 and Fluka-05120, ordered mesoporous carbon (CMK-3), and ordered mesoporous carbide-derived carbon (DUT-19). The experimental and thermodynamically predicted carbon deposition, the average and total hydrogen production, and the effect of flow rate on carbon formation rate of these catalysts were investigated. Results indicate that the experimental conditions chosen were within the reaction control regime. Catalytic activity was calculated via two different definitions present in literature: one in terms of carbon deposition rate and the other in terms of carbon mass deposited. Deactivation kinetics were obtained by fitting the experimental data by nonlinear regression analysis. Differences between the two methods in determining activity resulted in significant changes in the estimation of deactivation kinetics. The activity calculated based on the rate method results in the best fit of experimentally collected data. A deactivation order and methane concentration dependency of approximately 1.0 and 0.5 were determined for all the catalysts tested (Fluka-05105, Fluka-05120, CMK-3, and DUT-19). The activation energy of deactivation (Ed) was determined to be 192, 154, 166, and 181 kJ/mol for Fluka-05120, Fluka-05105, CMK-3, and DUT-19, respectively. DUT-19 was the best performing catalyst in terms of carbon formation rate, total carbon production, hydrogen production rate, average hydrogen production, and total hydrogen production. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20